2017
DOI: 10.1080/09712119.2017.1316278
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of digestible tryptophan:lysine ratios for maximum performance, egg quality and welfare of white-egg-laying hens by fitting the different non-linear models

Abstract: A total of 360 Hy-Line W-36 hens at 30 wk of age were assigned to 6 dietary treatments that consisted of 6 different (11, 15, 19, 23, 27 and 31) digestible Trp:Lys ratios. Hens were fed the experimental diets from 30 to 36 wk of age. Productive traits were recorded every wk and egg quality was measured at 36 wk of age. Total IgM, IgG, anti-sheep red blood cell antibody titres, plasma corticosterone, serotonine and glucose concentrations and heterophil to lymphocyte ratio (H:L) were determined at wk 6 of the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…It is considered that conventional layer diets contain sufficient tryptophan to meet requirements ( Mousavi et al., 2018 ); however, supplementation of feed-grade tryptophan may become necessary in diets with reduced crude protein and increased levels of feed-grade amino acids. Moreover, Dong et al.…”
Section: Importance Of Dietary Amino Acids In Laying Hensmentioning
confidence: 99%
See 3 more Smart Citations
“…It is considered that conventional layer diets contain sufficient tryptophan to meet requirements ( Mousavi et al., 2018 ); however, supplementation of feed-grade tryptophan may become necessary in diets with reduced crude protein and increased levels of feed-grade amino acids. Moreover, Dong et al.…”
Section: Importance Of Dietary Amino Acids In Laying Hensmentioning
confidence: 99%
“…Dietary tryptophan has positive impacts on feed intake, but results are too inconsistent to provide any estimations. However, it has been reported that layer hens offered diets with 1.56 g/kg or lower levels of tryptophan showed depressed feed intake ( Mousavi et al., 2018 ; Wen et al., 2019a ). However, Table 11 shows that dietary tryptophan was positively correlated with feed intake in layer hens (r = 0.554, P = 0.0012).…”
Section: Importance Of Dietary Amino Acids In Laying Hensmentioning
confidence: 99%
See 2 more Smart Citations
“…(2008) reported a Trp requirement of 120 mg/d of Trp relative to 482 mg/d of Lys based on broken line estimates using Hy-Line W-36 hens from 28 to 34 wk of age. A more recent publication estimated a higher requirement of 151 mg Trp/d relative to 675 mg/d of Lys based on 95 g/d intake of Hy-Line W-36 hens from 30 to 36 wk of age ( Mousavi et al., 2017 ). However, none of the previous experiments have investigated the requirement of Trp as the pullets are transitioning into egg production.…”
Section: Introductionmentioning
confidence: 99%